2017
DOI: 10.1016/j.bpj.2016.11.2089
|View full text |Cite
|
Sign up to set email alerts
|

Ultradonut Topology of the Nuclear Envelope

Abstract: The nuclear envelope is a unique topological structure formed by lipid membranes in eukaryotic cells. Unlike other membrane structures, the nuclear envelope comprises two concentric membrane shells fused at numerous sites with toroid-shaped pores that impart a "geometric" genus on the order of thousands. Despite the intriguing architecture and vital biological functions of the nuclear membranes, how they achieve and maintain such a unique arrangement remains unknown. Here, we used the theory of elasticity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…The NE consists of two lipid bilayer membranes, namely outer (ONM) and inner (INM) nuclear membranes, which are separated by a ∼35-50 nm perinuclear space. These membranes fuse together at the sites of Nuclear Pore Complex (NPC) giving rise to an ultra-donut topology [6]. Both NE components, notably LINC complexes (Linker of Nucleoskeleton and Cytoskeleton) and NPC may contribute to changes of mechanical properties of the nucleus in animals [7].…”
Section: The Three Structural Compartments Of the Nucleusmentioning
confidence: 99%
“…The NE consists of two lipid bilayer membranes, namely outer (ONM) and inner (INM) nuclear membranes, which are separated by a ∼35-50 nm perinuclear space. These membranes fuse together at the sites of Nuclear Pore Complex (NPC) giving rise to an ultra-donut topology [6]. Both NE components, notably LINC complexes (Linker of Nucleoskeleton and Cytoskeleton) and NPC may contribute to changes of mechanical properties of the nucleus in animals [7].…”
Section: The Three Structural Compartments Of the Nucleusmentioning
confidence: 99%
“…Nuclear shape is strongly dependent on intracellular and extracellular mechanical stimuli, including pressure difference across the nuclear membrane [96], cytoskeletal pre-stress [99], and topology of the nuclear envelope [100]. In higher eukaryotes, nuclear morphology is tightly regulated by nuclear lamina [101,102]. High resolution real time imaging [102] and micromanipulation of cell adhesion [39,104] have demonstrated that nuclear shape is systematically altered during cell migration through tight molecular interactions between the nuclear envelope and cytoskeletal components [10,89].…”
Section: Mechanism Of Nuclear Remodeling During Cell Migrationmentioning
confidence: 99%
“…A yet unmet challenge in the SLB field is the in vitro reconstruction of more complex biological membranes, such as the nuclear envelope. The nuclear envelope is a double membrane, 121 in which transmembrane proteins couple the inner membrane to chromatin and the outer membrane relays signals from the cytoskeleton. 122 Such an in vitro model would allow the study of the molecular basis of epigenetic mechanisms and nuclear envelope membrane repair in physiological and diseased contexts.…”
Section: Engineering Curved Membranes To Understand the Mechanisms Ofmentioning
confidence: 99%